Development of Learning Media Based on Toontastic Animation Video on Theme 5 Pahlawanku Class IV SD Negeri 060874 Medan Perjuangan District - Sihombing, Wahyu; Tambunan, Husna Parluhutan; Sitohang, Risma; Siregar, Arifin; Simanihuruk, Lidia (Indonesian Journal of Advanced Research, 2023)
This research aims to see the results of developing learning media based on Toontastic animated videos on theme 5, sub-theme 1, learning 1 Class IV, SD Negeri 060874, Medan Perjuangan District. Toontastic Animation Video-Based Learning Media was developed through the R&D (Research and Development) method with the development model being ADDIE (Analysis, Design, Development, Implementation, Evaluation). The Toontastic Animation Video-Based Learning Media developed has reached the effectiveness criteria because it can be applied well to students. Based on the results of the tests carried out, it is known that the pre-test average is 35, while the average post-test score is 90. This shows that students' post-test results have improved compared to the pre-test. The percentage of post-test scores is 90% in the category "Very Effective so that Toontastic Animation Video Based Learning Media in theme 5 sub theme 1 learning 1 class IV is very effective to be applied to the teaching and learning process.